2012
DOI: 10.1007/s12275-012-1362-8
|View full text |Cite
|
Sign up to set email alerts
|

Microbial fingerprinting detects unique bacterial communities in the faecal microbiota of rats with experimentally-induced colitis

Abstract: An abnormal composition of the gut microbiota is believed to be associated with the pathogenesis of inflammatory bowel disease (IBD). We utilized terminal restriction fragment length polymorphism (T-RFLP) analysis to quantify faecal bacterial communities from rats with experimental colitis. Male Sprague Dawley rats (n=10/group) ingested 2% dextran sulfate sodium (DSS) or water for up to 7 days. Rats were killed and colonic tissues collected for histological analysis. Damage severity score in the distal colon w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 46 publications
4
30
0
Order By: Relevance
“…Alpha diversity is usually used to reflect the richness or diversity of bacterial community. Many studies have reported that DSS treatment caused decline in the bacterial diversity of fecal samples (Akira et al., ; Samanta, Torok, Percy, Abimosleh, & Howarth, ), whereas Lactobacillus intervention can improve the diversity (RodrĂ­guez‐Nogales et al., ). This situation was similar to our results in caecal contents, although we failed to observe any statistical significance among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha diversity is usually used to reflect the richness or diversity of bacterial community. Many studies have reported that DSS treatment caused decline in the bacterial diversity of fecal samples (Akira et al., ; Samanta, Torok, Percy, Abimosleh, & Howarth, ), whereas Lactobacillus intervention can improve the diversity (RodrĂ­guez‐Nogales et al., ). This situation was similar to our results in caecal contents, although we failed to observe any statistical significance among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…and Lactobacillus sp. were predominantly associated with the DSS-induced colitic and healthy rats, respectively [30]. Obviously, there were significant differences between the experimental sets from which samples were sourced.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these observations in MutY 2/2 mice, it is possible that MUTY-mediated repair of misincorporated adenines across from 8-oxoG lesions may in fact be the trigger for colon carcinogenesis susceptibility in the OGG1-deficient background [Liao et al, 2008]. Additionally, it is now becoming clear that factors such as the composition of the gut microbiome may influence the severity of DSSinduced colitis [Rath et al, 2001;Berry et al, 2012;Lombardi et al, 2012;Samanta et al, 2012;De Fazio et al, 2014]. The gut microbiome composition has also been linked to risk for diseases such as obesity [reviewed in Ohtani et al, 2014].…”
Section: Inflammationmentioning
confidence: 99%